Missed opportunities in the way medical schools evaluate the ethical domain in clerkship rotations - Dos Santos, Maria Fernanda [UNESP]; Schoueri, João F.L. [UNESP]; Vidal, Camila T. [UNESP]; Filho, Pedro T. Hamamoto [UNESP]; Fukushima, Fernanda B. [UNESP]; Vidal, Edison I.O. [UNESP] (Public Library of Science (PLoS), 2019)
Background Several lines of evidence indicate that medical schools have been failing to adequately nurture empathy and the ethical dimension in their graduates, the lack of which may play a central role in the genesis of medical errors, itself a major source of avoidable deaths, incapacity and wasted resources. It has been widely proposed that medical schools should adopt evaluation strategies as a means to promote a culture of respectful relationships. However, it is not clear if evaluation strategies in medical schools have addressed key domains related to that aim, such as ethics, through the perspective of their students. Hence, we conducted a national survey of instruments used by Brazilian medical schools to assess clerkship rotations from the perspective of students, with a main focus on the ethical domain. Methods The authors invited 121 randomly selected institutions to participate in the study. Key informants answered a questionnaire about clerkship rotations and sent copies of any instrument used to assess the quality of clerkship rotations according to the students' perspectives. Results Twenty-six (53%) of 49 participating schools used an instrument to assess the quality of clerkship rotations according to the perspective of students. Just 13 (27%) schools had instruments containing at least one question encompassing the ethical domain. Only 2 (4%) schools asked students specifically about the occurrence of any negative experience concerning the ethical domain during rotations. Merely 1 (2%) school asked students about having witnessed patient mistreatment and none asked about mistreatment against students themselves. Conclusions There are several missed opportunities in the way medical schools assess the quality of clerkship rotations regarding the ethical domain. Closing the gap between usual institutional discourses regarding ethics and how that dimension is assessed within clerkship rotations might represent an important step towards the improvement of medical education and healthcare systems.